Screening for autism spectrum disorder in deaf adults with intellectual disability: Feasibility and accuracy of two autism screening instruments. (March 2022) - Hofer, J.; Tillmann, J.; Salzmann, J.; Bölte, S.; Fellinger, J.; Holzinger, D.
Highlights: The PDD-MRS and the DiBAS-R are valid ASD screening tools for individuals with deafness. Only minimal adaptation of item interpretation in the context of deafness is required. Items referring to reciprocal social interaction are highly discriminant between individuals with and without ASD. Abstract: Abstract background: There is a lack of autism screening instruments for deaf or hard of hearing (DHH) adults with intellectual disability. Aims: This study examined the diagnostic validity of the Pervasive Developmental Disorder in Mental Retardation Scale and the Diagnostic Behavioral Assessment for autism spectrum disorder – Revised in this rare population. Methods and participants: 56 DHH adults with intellectual disability living in three specialized therapeutic communities were examined, 9 of whom met criteria for autism. Outcomes and results: With minimal adaptions regarding item interpretation, both tools showed good diagnostic and high convergent validity. Items probing for difficulties in reciprocal social interaction and restricted interests were discriminant between individuals with and without autism. Conclusion: These data suggest that both autism screening tools are feasible and psychometrically sound when used with appropriate adaptations for DHH adults with intellectual disability.